2014
DOI: 10.1002/2013jd020131
|View full text |Cite
|
Sign up to set email alerts
|

Twomey effect observed from collocated microphysical and remote sensing measurements over shallow cumulus

Abstract: Clear experimental evidence of the Twomey effect for shallow trade wind cumuli near Barbados is presented. Effective droplet radius (reff) and cloud optical thickness (τ), retrieved from helicopter‐borne spectral cloud‐reflected radiance measurements, and spectral cloud reflectivity (γλ) are correlated with collocated in situ observations of the number concentration of aerosol particles from the subcloud layer (N). N denotes the concentration of particles larger than 80 nm in diameter and represents particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 37 publications
5
63
0
Order By: Relevance
“…(2001) investigated aerosol-cloud relationships over the Indian Ocean and found only a slight increase in the mean ACI N values from 0.63 to 0.67 and 0.7 for data sets, considering only data for which the vertical winds were < 0.5, > 0.5-2, and > 2 m s −1 in tropical cloud layers, respectively. Werner et al (2014) found that updraft velocity variations from 0.5 to 4 m s −1 caused variations in the derived ACI r values by 0.02 and in ACI N by 0.06. They concluded that updraft velocity strength is of minor importance in aerosol-cloud interaction studies of short-lived tropical trade-wind cumuli over the tropical Atlantic.…”
Section: Aci N From Airborne Observationsmentioning
confidence: 90%
See 1 more Smart Citation
“…(2001) investigated aerosol-cloud relationships over the Indian Ocean and found only a slight increase in the mean ACI N values from 0.63 to 0.67 and 0.7 for data sets, considering only data for which the vertical winds were < 0.5, > 0.5-2, and > 2 m s −1 in tropical cloud layers, respectively. Werner et al (2014) found that updraft velocity variations from 0.5 to 4 m s −1 caused variations in the derived ACI r values by 0.02 and in ACI N by 0.06. They concluded that updraft velocity strength is of minor importance in aerosol-cloud interaction studies of short-lived tropical trade-wind cumuli over the tropical Atlantic.…”
Section: Aci N From Airborne Observationsmentioning
confidence: 90%
“…The studied short-lived cumuli fields or aged stratocumulus layers mostly develop within a well-mixed, undisturbed marine boundary layer at almost adiabatic-like stratification of the water content resulting in an height-independent CDNC from cloud base to top (Painemal and Zuidema, 2013). Effects of vertical motions (updrafts, turbulent mixing, and entrainment of drier air into the clouds) may then be comparably weak (Twohy et al, 2005;Terai et al, 2012;Werner et al, 2014). In contrast, much more complex aerosol and meteorological conditions occur over land, as mentioned above.…”
Section: Aci N From Satellite Remote Sensingmentioning
confidence: 99%
“…Such constellations are well suited to investigate the interaction of cloud microphysical and radiative properties as demonstrated by Werner et al (2014) for shallow cumulus. However, the approach by Werner et al (2014) for analysing the collocated number concentration and cloud remote sens- ing works only if the radiation measurements are taken well above the cloud.…”
Section: Collocation Of Microphysical and Radiative Propertiesmentioning
confidence: 99%
“…However, the approach by Werner et al (2014) for analysing the collocated number concentration and cloud remote sens- ing works only if the radiation measurements are taken well above the cloud. In the case of the AIRTOSS-Learjet tandem this would limit the analysis to the uppermost cirrus layer.…”
Section: Collocation Of Microphysical and Radiative Propertiesmentioning
confidence: 99%
See 1 more Smart Citation